2013
DOI: 10.5039/agraria.v8i3a2288
|View full text |Cite
|
Sign up to set email alerts
|

Fertirrigação com biofertilizante bovino: Efeitos no crescimento, trocas gasosas e na produtividade do pinhão-manso

Abstract: RESUMOObjetivou-se, aqui, avaliar o crescimento, as alterações nas trocas gasosas e a produtividade do pinhão-manso fertirrigado com diferentes concentrações de biofertilizante bovino. O estudo foi realizado na área experimental da UFC, em Fortaleza-CE. O delineamento experimental foi em blocos casualizados com cinco tratamentos e cinco repetições. Os tratamentos utilizados foram: T1 = 0% (testemunha), T2 = 12,5%, T3 = 25%, T4 = 50% e T5 = 100% do biofertilizante. Foram analisadas as seguintes variáveis: altur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 10 publications
1
12
0
15
Order By: Relevance
“…Cavalcante et al (2010) also found a high PDM in the presence of the biofertilizer in relation to 0.5 dS/m³ water for guava seedlings. According to Sousa et al (2013), the biofertilizer provides an increase in photosynthetic rate and chlorophyll. This results in a greater assimilation and fixation of CO 2 , producing mass of total plant dry matter (PDM), which may have occurred in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Cavalcante et al (2010) also found a high PDM in the presence of the biofertilizer in relation to 0.5 dS/m³ water for guava seedlings. According to Sousa et al (2013), the biofertilizer provides an increase in photosynthetic rate and chlorophyll. This results in a greater assimilation and fixation of CO 2 , producing mass of total plant dry matter (PDM), which may have occurred in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Na tampa das mesmas foi adaptada uma mangueira com a outra extremidade mergulhada num recipiente com água na altura de 20 cm, para a saída de gases (SOUSA et al, 2013).…”
Section: Introductionunclassified
“…The bovine biofertilizer has a positive action, acting in the improvement of the soil quality in terms of aeration, besides the supplying of nutrients and organic matter to the plants. In addition, the WATER SALINITY AND BOVINE BIOFERTILIZER IN THE PRODUCTION OF EGGPLANT SEEDLINGS biofertilizer has many beneficial substances, among them humic substances, which promote the reduction of the osmotic potential of the soil solution, stimulating the absorption of water and nutrients by the plants in saline environments (SOUSA et al, 2013a).…”
Section: Figurementioning
confidence: 99%